A 2D Cu(II)-based coordination polymer: treatment effect on Parkinson's disease by increasing dopamine and VMA content. Issue 10 (10th August 2020) - Zhu, Peng-Bo; Ke, Zun-Liang; Won, Hyung-Sun; Tan, Songyin
Abstract: By using a mixed-ligand approach, a new Cu(II)-based coordination polymer with the chemical formula of [Cu(4-dpds)(bdc)(H2 O)2 ] · 4-dpds (1 ) (4-dpds = 4, 4′-dipyridyldusulfide and H2 bdc = benzenedicarboxylic acid) has been synthesized and structurally determined by single-crystal X-ray diffractometer, powder X-ray diffraction, elemental analysis, infrared spectra and thermogravimetric analysis. Furthermore, the treatment effect of the synthetic compound was evaluated on the Parkinson's disease animal model and the enzyme linked immunosorbent assay (ELISA) was performed to detect the content of dopamine content in the substantia nigra. Then, the high efficiency liquid phase chromatogram (HPLC) was conducted for the measurement of the vanillyl mandelic acid (VMA) in urine.